INDUCED DRAFT COOLING TOWER PERFORMANCE RESULTS USING CHARACTERISTIC CURVE METHOD - Al Aisy, Rihadatu
This project studies the performance and capabilities of an Induced Draft Counter Flow Cooling Tower. This study starts with the geothermal plant. During the process of generating power, a geothermal plant will produce excess heat. This is where the cooling tower comes into play, it helps the system get rid of this heat. This study also explores basic principles and theories about cooling towers. The evaluation of this tower is performed using the characteristic method. In this method there are four main parameter values to be found. These are the test liquid to gas ratio, test tower characteristic, predicted liquid to gas ratio, and finally the capabilities. When obtaining these values other performance values will be found too. The methodology used adheres to the Cooling Tower Institute’s code titled “Acceptance Test Code for Water Cooling Towers” CTI ATC-105 Code. This code also provides a computer program to help obtain more reliable and precise psychrometric data. The subject of the project is to find and compare two cases of cooling tower performances. One cooling tower is at peak performance giving a capability of 100.96%. While the other has some disturbances resulting in a significantly reduced performance of 85.85% capability. One cooling tower removes heat better than the other. This shows that sometimes slight disturbances could drastically affect performance.